Indication of p + 11B reaction in Laser Induced Nanofusion experiment - N. Kroó; L. P. Csernai; I. Papp; M. A. Kedves; M. Aladi; A. Bonyár; M. Szalóki; K. Osvay; P. Varmazyar; T. S. Biró; (for the NAPLIFE Collaboration) (Scientific Reports)
Abstract The NanoPlasmonic Laser Induced Fusion Energy (NAPLIFE)1 project proposed fusion by regulating the laser light absorption via resonant nanorod antennas implanted into hydrogen rich urethane acrylate methacrylate (UDMA) and triethylene glycol dimethylacrylate (TEGDMA) copolymer targets. In part of the tests, boron-nitride (BN) was added to the polymer. Our experiments with resonant nanoantennas accelerated protons up to 225 keV energy. Some of these protons then led to p + 11B fusion, indicated by the sharp drop of observed backward proton emission numbers at the 150 keV resonance energy of the reaction. The generation of alpha particles was verified by CR-39 (Columbia Resin #39) nuclear plastic track detectors.